Melioidosis: Is it still underdiagnosed? - Vasantha Kamath; M Priyanka; Deepthi Reddy (Wolters Kluwer Medknow Publications, 2024)
Burkholderia pseudomallei, a Gram-negative bacterium, is the cause of Melioidosis, a disease that is known to cause significant morbidity and mortality in Southeast Asia. It is also classified as a potential biological warfare agent and is considered a category B priority pathogen. Despite being common in these areas, melioidosis is often underdiagnosed due to lack of awareness of its clinical and microbiological characteristics, limited health-care resources, and the varied ways in which it can present. It is important to recognize the clinical features of melioidosis early on and properly manage the disease to reduce its impact.